Analysis of Academic Procrastination Language in Thesis Completion : Case Study of Psychology Students at Islamic University of Riau - Muhammad Rivansyah Nugraha Putra; Wina Diana Sari (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2024)
People that procrastinate do so in an effort to stay in their comfort zones. Academic procrastination during thesis work emerges as a result of misunderstanding and difficulty in the work. goals of the research Using a qualitative case study approach combined with in-depth interviews, the research aims to determine the prevalence of procrastination in thesis work among students at the Islamic University of Riau, Faculty of Psychology, as well as the factors that contribute to procrastination. The study involves five students from the Faculty of Psychology. Furthermore, purposive sampling was employed, while interviews and observation were the data-gathering techniques. The study's findings indicate that the primary causes of academic procrastination include a lack of desire, trouble managing time, trouble finding references, beginning research methodology, financial restraints, and a concentration on more pleasurable activities. In addition, there are internal and external factors are indicated to this study results.